Mitochondrial Encephalo-Myopathy, Lactic Acidosis and Stroke Like Syndrome (MELAS): A Case Report - Islam, Kazi Ashraful; Rahman, Md Misanur; Akhter, Shaheen; Alam, Syeda Tabassum; Mutanabbi, Mahbub (Bangladesh Journal of Child Health, 2010)
DOI: 10.3329/bjch.v33i3.5692 Bangladesh Journal of Child Health 2009; Vol.33(3): 111-113